Factors affecting pain in acute ankle fractures: A prospective evaluation. Issue 8 (August 2015) - Saper, David; Litrenta, Jody; Otlans, Peters; Daley, James; Tornetta, Paul
Abstract Pain has been identified as the dominant factor in patient outcomes. The purpose of this study was to evaluate the degree of pain reported in a large series of acute ankle fractures and to determine what factors are associated with higher pain scores. We prospectively evaluated 457 consecutive patients with acute Weber B supination external rotation ankle fractures upon presentation for pain in 9 areas of the ankle. There were 231 females and 226 males, average age 46.2 (18–96) with 133 bi/tri-malleolar and 324 lateral malleolar fractures. There were 101 SE2, 73 stress (+) SE4, and 150 ligamentous SE4 injuries. The highest pain score (VAS 0–10) for the medial and lateral regions was chosen for analysis. Other factors included in the multivariate analysis were: age, ethnicity, DM, alcohol presence, and days from injury to presentation on the level of pain reported using a linear regression model and set statistical significance at 0.05. In univariate analysis, the type of injury (medial malleolus or deltoid ligament) nor instability differed with respect to medial pain. However, patients presenting with instability had more lateral pain (5.6 ± 3) than those with stable injuries (2.6 ± 3) (p < 001). Additionally, those with bony medial injury had more lateral pain (7 ± 2.7) than those with isolated lateral malleolar fractures (4.0 ± 3.4) (p < 0.001). Most importantly, in the multivariate analysis, the only factor that was significant for both medial and lateral pain (separate regressions) was ethnicity, with blacks having more pain given the same injury than whites (p < 0.001). Latinos trended towards having more lateral pain than whites (p = 0.15), but not more medial pain (p = 0.3). For lateral pain, in addition to ethnicity, presence of a displaced mortise (p < 0.0001), having a medial bony injury (p < 0.0001), and the days from injury (p = 0.008) were significant. Pain decreased with time from injury. In this evaluation of over 450 patients with Weber B, SE pattern ankle fractures we confirmed previous work in the upper extremity indicating an important difference in the reported pain by ethnicity. In particular, black patients have more pain than white or latino patients given the same injury.